Genetic, physiological, and gene expression analyses reveal that multiple QTL enhance yield of rice mega-variety IR64 under drought - Swamy, B.P. Mallikarjuna; Ahmed, Helal Uddin; Henry, Amelia; Mauleon, Ramil; Dixit, Shalabh; Vikram, Prashant; Tilatto, Ram; Verulkar, Satish B.; Perraju, Puvvada; Mandal, Nimai P.; Variar, Mukund; Robin, S.; et al. (Public Library of Science, 2013)
Rice (Oryza sativa L.) is a highly drought sensitive crop, and most semi dwarf rice varieties suffer severe yield losses from reproductive stage drought stress. The genetic complexity of drought tolerance has deterred the identification of agronomically relevant quantitative trait loci (QTL) that can be deployed to improve rice yield under drought in rice. Convergent evidence from physiological characterization, genetic mapping, and multi-location field evaluation was used to address this challenge.